Hybrid electric aircraft propulsion case study for skydiving mission - Glassock, Richard; Galea, Michael; Williams, Warren; Glesk, Tibor (MDPI, 2017)
This paper describes a case study for applying innovative architectures related to electrified propulsion for aircraft. Electric and hybrid electric propulsion for aircraft has gained widespread and significant attention over the past decade. The driver for industry interest has principally been the need to reduce emissions of combustion engine exhaust products and noise, but increasingly studies revealed potential for overall improvement in energy efficiency and mission flexibility of new aircraft types. In this work, a conceptual new type for a skydiver lift mission aircraft is examined. The opportunities which electric hybridisation offers for this role is analysed in comparison with conventional legacy type propulsion systems. For a conventional commercial skydiving mission, an all-electric propulsion system is shown as viable, and a hybrid-electric system is shown to reduce aircraft fuel costs and CO2 emissions whilst maintaining conventional aero-engine operational benefits. The new paradigm for aircraft development which hybrid electric propulsion enables has highlighted significant issues with aircraft certification practices as they exist today. The advancement of aircraft design and production to harness the value of new propulsion systems may require adaption and development of certification standards to cater for these new technologies.